Causas da redução da firmeza de polpa e de alterações na epiderme em Caqui Fuyu - Souza, Edson Luiz de (2010)
Among the most common problems mentioned by traders of 'Fuyu' persimmon, are physiological disorders, such as epidermal browning, degeneracy and pulp firmness reduction. But we still do not have available a quantification of these problems, either the causes or preventive measures. In this context, during the 2007-2010 period was carried out a series of experiments in order to: 1) perform diagnosis, at least in part, of persimmons quality of this cultivar produced in the states of SC, PR, RS; 2) assess technological responses by applying nitrogen (N) at pre-harvest, a practice commonly employed to increase productivity, 3) monitor changes in sugar accumulation and its correlation with the production region and the occurrence of skin cracks and 4) study the acclimation effect of fruits before cold storage as a means to induce increased tolerance to cold. Of this set of experiments we observed that indeed there are significant physiological disorders in 'Fuyu' persimmons, but the exact cause was not put in evidence. Probably, this is a multifactorial response resulting from the mineral nutrition, weather conditions and plant management. Regarding N suplementation, it was found that this macronutrient contributes to the increasing on number of fruits per plant and productivity, without compromising the overall quality, except the color that remains less orange and the decrease in pulp firmness at higher doses. When compared to fruit 'Fuyu' persimmon orchards with different altitudes, it was found that those from higher altitudes accumulate higher concentrations of sugars, including sorbitol, detecting a higher incidence of skin cracks. Finally, it was shown that the persimmons acclimation at 23 ± 3 °C for two days be fore the cold storage stimulates a higher accumulation of putative genes transcripts of HSPs cytosolic, mitochondrial, chloroplastic and of endomembranes transport system, higher accumulation of expansins and enzymes involved in cell wall solubilization, resulting in an appropriate evolution of ripening after refrigerated storage. These results bring a significant contribution to the technological knowledge in order that it is a treatment pre-storage, easily applied by producers and hosts of persimmons.